Fasciitis Necroticans after Elective Hernia Inguinal Surgery. (5th January 2014) - Sigterman, T. A.; Gorissen, Kim J.; Dolmans, Dennis E. J. G. J.
Abstract : Necrotising fasciitis is a rare but disastrous complication after elective surgery. We present two patients (both male, 58 and 18 years old) who developed necrotising fasciitis following elective inguinal hernia repair according to Lichtenstein. The importance of both recognition and time interval between symptom occurrence and surgical intervention is illustrated, emphasising the need for immediate action when necrotising fasciitis is suspected. A high index of suspicion of necrotising fasciitis should be maintained when a wound infection is accompanied by disproportional pain, lethargy, or sepsis. Epidermolysis and subcutaneous emphysema are often very late symptoms. Recognition and immediate intervention decrease mortality and morbidity.